miR-155 Is Essential for Inflammation-Induced Hippocampal Neurogenic Dysfunction - Woodbury, Maya E. (J Neurosci, 2015)
Peripheral and CNS inflammation leads to aberrations in developmental and postnatal neurogenesis, yet little is known about the mechanism linking inflammation to neurogenic abnormalities. Specific miRs regulate peripheral and CNS inflammatory responses. miR-155 is the most significantly upregulated miR in primary murine microglia stimulated with lipopolysaccharide (LPS), a proinflammatory Toll-Like Receptor 4 ligand. Here, we demonstrate that miR-155 is essential for robust IL6 gene induction in microglia under LPS stimulation in vitro. LPS-stimulated microglia enhance astrogliogenesis of cocultured neural stem cells (NSCs), whereas blockade of IL6 or genetic ablation of microglial miR-155 restores neural differentiation. miR-155 knock-out mice show reversal of LPS-induced neurogenic deficits and microglial activation in vivo. Moreover, mice with transgenic elevated expression of miR-155 in nestin-positive neural and hematopoietic stem cells, including microglia, show increased cell proliferation and ectopically localized doublecortin-positive immature neurons and radial glia-like cells in the hippocampal dentate gyrus (DG) granular cell layer. Microglia have proliferative and neurogenic effects on NSCs, which are significantly altered by microglial miR-155 overexpression. In addition, miR-155 elevation leads to increased microglial numbers and amoeboid morphology in the DG. Our study demonstrates that miR-155 is essential for inflammation-induced neurogenic deficits via microglial activation and induction of IL6 and is sufficient for disrupting normal hippocampal development.